Quality of Service and Quality of Experience Measurements on IP Multicast Based IPTV Systems - Lencse, G.; Steierlein, B. (Acta Technica Jaurinensis, 2012)
The essential protocols of IP multicast based IPTV systems (IGMP, PIMSM) are introduced. The operation of the IP multicast based IPTV systems is demonstrated on a small test network. The bandwidth requirement of the multicast and unicast based IPTV systems are compared. The value of different Quality of Service parameters (packet loss, jitter, IGMP latency) and their effect to the Quality of Experience are measured.